1972
DOI: 10.1111/j.1365-2222.1972.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible modes of action of ACTH and glucocorticoids in allergic diseases

Abstract: In vivo observations of the effects of cortisone on the vascular reactions to large doses of horse serum using the rabbit ear chamber technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 162 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…Steroids have been shown in vitro to stabilise lysosomal membranes (Weissmann, 1964;Henson, 1971 ;Ignarro, Oronsky and Perper, 1973) and prevent the mobilisation and extracellular release of lysosomal enzymes from phagocytosing leucocytes (Wright and Malawista, 1973). In addition to these actions, it has also been suggested that steroids might act via a local effect upon the reactivity of the tissues by an increase in vascular tone (Jasani, 1972) or even by a systemic action on the complement system (Gewurz, Werwick, Quie and Good, 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids have been shown in vitro to stabilise lysosomal membranes (Weissmann, 1964;Henson, 1971 ;Ignarro, Oronsky and Perper, 1973) and prevent the mobilisation and extracellular release of lysosomal enzymes from phagocytosing leucocytes (Wright and Malawista, 1973). In addition to these actions, it has also been suggested that steroids might act via a local effect upon the reactivity of the tissues by an increase in vascular tone (Jasani, 1972) or even by a systemic action on the complement system (Gewurz, Werwick, Quie and Good, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration was determined using the method of Lowry, Roseborough, Farr and Randall (1951).…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…Xylometazoline hydrochloride possesses a topical decongestant effect on the nasal mucosa (8). The corticosteroid drug, Dexamethasone 21-isonicotine, can possibly suppress some types of antigen-antibody reaction (7,10), and one of its side-effects is topical decongestion of the mucosa. However, the whole role and the details of the mode of action of corticosteroids on the various types of the antigen-antibody reaction are not yet fully known.…”
Section: Discussionmentioning
confidence: 99%
“…An alpha-sympathomimetic agent was chosen as a known topical decongestant of the nasal mucosa. Corticosteroids may suppress some types of antigenantibody reaction (7,10) and one of their side-effects is topical decongestion.…”
mentioning
confidence: 99%
“…[41]. However, the field has not been well studied, and in most experi ments, reviewed recently by Jasani [15], no consistent effects of steroids on histamine release were demonstrated. We observed inhibition of LCP-mediated histamine release by several glucocorticosteroids at con centrations from 10'8-2 X 1 0 '5 M. The effects were quite variable de pending on the animal used.…”
Section: Discussionmentioning
confidence: 99%